Professional Requirement and Competitive Practices of Listed Companies in Stock Market (Socio-Economic Development Panorama, 2008)
Listed companies in stock market is moving towards enhancement of professional quality to meet the existant challenges of double digit growth rate that Nepal currently aspires. The article eloquently dwells upon the lacunas and obstacles prevalent to ensuring a healthy profesional competative environment so as to invigorate a vibrant stock market practices. The methodology of professionalsim requirement helps to ensure a sound indigenous and foreign investment in the stock market. This is intricatly tied up with building up legitimate practices aimed towards invigorting a vibrant market oriented system by accepting a harmonious corporate responsibilites and dissemination of a transparent transactions. Herein, institutionalization of a healthy and a growth oriented strategic mechanism helps to address an investor friendly attitude. The article dwells upon the undercurrent categoriazation of the listed companise into A, B, C, and points out to the pitfalls of stock market mechanism. Only when adopting an investor firendly climate will it ultimately help to accelerate the pace of development. It also advocates steps to usher into building a healthy promotional mechanism through maintainance of professional ethics, practice of a sound managment system, and cultivate efficiency of the executive sector. This is possible only thorugh institutional strengthening by adopting democratic investment practices through follow up of the corporate rules and regulations can the enlisting companies leap frog and thus create a favourable impact for a double digit growth trajectory. Keywords: professional requirement, companies in stock market, market oriented strategy, investment practices, security dealings, structural adjustment program, stock ownership, professional integrity, investor friendly, company categorization, performance culture Socio Economic Development Panorama, Vol. 1, No. 3(2008) pp. 31-48